Nematophagous fungi: Far beyond the endoparasite, predator and ovicidal groups - Soares, Filippe Elias de Freitas; Sufiate, Bruna Leite; Queiroz, José Humberto de (Agriculture and Natural Resources, 2018)
Knowledge of nematophagous fungi has increased dramatically over recent years, particularly with the advancement of molecular biology and omics sciences. However, most of this knowledge is restricted to the three traditional groups of nematophagous fungi: predatorial, opportunistic or ovicidal and endoparasitic. The present study supported the proposed classification of nematophagous fungi into five groups: nematode-trapping/predators, opportunistic or ovicidal, endoparasites, toxin-producing fungi and producers of special attack devices. This study also highlighted the analogy between special attack devices and real medieval weapons. Much study remains to be done to better understand some fungi and to discover new fungi with nematophagous and biological control potential.